2016
DOI: 10.1007/s13398-016-0324-0
|View full text |Cite
|
Sign up to set email alerts
|

Almost square and octahedral norms in tensor products of Banach spaces

Abstract: Abstract. The aim of this note is to study some geometrical properties like diameter two properties, octahedrality and almost squareness in the setting of (symmetric) tensor product spaces. In particular, we show that the injective tensor product of two octahedral Banach spaces is always octahedral, the injective tensor product of an almost square Banach space with any Banach space is almost square, and the injective symmetric tensor product of an octahedral Banach space is octahedral.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(41 citation statements)
references
References 17 publications
1
40
0
Order By: Relevance
“…In [1, Question b)] it is asked how are the diameter two properties, in general, preserved by tensor product spaces. Corollary 5.11 yields new examples of injetive tensor products with the slice-D2P different from those obtained in [2, Theorem 5.3] and of [22,Theorem 2.6].…”
Section: Alsomentioning
confidence: 87%
“…In [1, Question b)] it is asked how are the diameter two properties, in general, preserved by tensor product spaces. Corollary 5.11 yields new examples of injetive tensor products with the slice-D2P different from those obtained in [2, Theorem 5.3] and of [22,Theorem 2.6].…”
Section: Alsomentioning
confidence: 87%
“…In [21] it is shown that if X and Y are Banach spaces whose norms are octahedral then the norm of X ⊗ ε Y is also octahedral. The following proposition is similar to [ Proof.…”
Section: Octahedrality In Injective Tensor Productsmentioning
confidence: 99%
“…The following theorem provides a partial positive answer to [21,Question 4.4], where it is asked whether octahedrality is preserved by taking projective tensor products from one of the factors. Theorem 4.3.…”
Section: Octahedrality In Projective Tensor Productsmentioning
confidence: 99%
See 1 more Smart Citation
“…(2) Previous result has an immediate consequence in terms of octahedrality in Lipschitz-free Banach spaces. Recall that a Banach space X is said to have an octahedral norm if for every finite-dimensional subspace Y and for every ε > 0 there exists x ∈ S X verifying that y + λx > (1− ε)( y + |λ|) for every y ∈ Y and λ ∈ R. Notice that, given Banach spaces X and Y under the assumption of Proposition 2.11, it follows that F((B X * , ω • · ), Y * ) = F((B X * , ω • · )) ⊗ π Y * has an octahedral norm because of [19,Corollary 2.9]. Notice that this gives a partially positive answer to [3, Question 2], where it is wondered whether octahedrality in vector-valued Lipschitz-free Banach spaces actually relies on the scalar case.…”
Section: And Only If the Following Three Conditions Holdmentioning
confidence: 99%